(3LRGA GdcQes ((3GdbGgQIs (3hKjbIs, 2006)
(3GdcQeef NUGd GdNjQ,jLYd GdfGS eJYGhfjf eJMGHjf hdcf cQjekG cGf CSeG Ydj eSej jcQe Vjag jDOj Mbg(B..(3jYdj TCfg(B..(3Edj Cf LGA Vja eGPG MOK?gd MOK ecQhg?gd QaV cQje EcQGe Vjag(B..(3dG(B..(3dG(B..(3dGs
(3GdbUI(B--s (3GdfTjO(B--s (3dYHI GdMQha GdCHLOjI(B--s (3dYHI GdCTjGA(B--s (3dYHI GdJdhjfs
(3ef (B4 (3Edj (B9 (3SfhGJs
2
Keywords: (3GdcQes -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs